Health effects and mediating mechanisms of smart wearable devices on older people: evidence from China - Guo, Enkai; He, Shiyi; Zheng, Lan (Frontiers in Public Health, 2025)
BackgroundWith the aging of the population, health issues among older people have drawn increasing societal attention. The rapid development of intelligent technology provides innovative solutions to addressing these challenges. This study aims to explore the impact of smart wearable devices on older people’s health outcomes while discussing the mechanism of physical exercise, to provide a new perspective and exercise strategy for maximizing the positive role of smart wearable devices in older adult health management.MethodsUtilizing data from the China Longitudinal Aging Social Survey (CLASS), this study analyzed 21,881 samples. Descriptive statistics was computed using SPSS, followed by bidirectional fixed effect model analysis and intermediate effect test via Stata.ResultsBidirectional fixed effect model showed that the use of smart wearable devices could significantly improve the physical health of the older people (β = 0.325, p < 0.001). The effect was more significant in those aged 70 years or older (β = 0.385, p < 0.001), those without chronic diseases (β = 0.590, p < 0.001), and those living with their children (β = 0.452, p < 0.001). The mediating mechanism test results reported that exercise frequency (β = 0.037, p < 0.05) and exercise duration (β = 0.063, p < 0.001) were two positive mediating pathways for smart wearable devices to affect the health of the older adults.ConclusionThis study reveals the positive impact of smart wearable devices on the physical health level of the older people. To maximize benefits, we propose a dual-path optimization strategy: (1) Develop age-appropriate functions and use methods to improve device accessibility among older adult people, and (2) Generate a personalized exercise prescription for the older people to promote regular physical activity and exercise habits to improve their health level.